The Influence of Islamic Business Ethics and Service Quality on Customer Satisfaction (Case Study of Dina Muslimah Salon) - Naila Putri; Riyan Pradesyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid growth of business in Indonesia encourages entrepreneurs to innovate and compete in attracting consumers. One of the emerging sectors is Sharia-based businesses, including Muslimah beauty salons. These salons adhere to Islamic principles, such as using halal products and providing services according to Sharia guidelines. However, many still face challenges related to service quality and the implementation of Islamic business ethics, which impact customer satisfaction. This study analyzes the influence of Islamic business ethics and service quality on customer satisfaction at Salon Muslimah Dina. A quantitative approach was used with multiple linear regression analysis. Data were collected through questionnaires distributed to salon customers. The regression results show that Islamic business ethics and service quality significantly affect customer satisfaction, with an R Square value of 0.795, indicating that 79,5% of customer satisfaction can be explained by these variables. The ANOVA test confirms the model's significance with an F-value of 120.171 and a significance level of 0.000. Furthermore, regression coefficients indicate that service quality has a more dominant influence (B = 0.437, p < 0.05) than Islamic business ethics. These findings contribute to customer satisfaction theories in Sharia-based businesses and provide practical insights for business owners to improve Islamic-based services. By consistently applying Islamic business ethics and enhancing service quality, Muslimah salons can maintain customer loyalty and strengthen their competitive advantage. Future research may explore other factors influencing customer satisfaction, such as pricing strategies, marketing approaches, and service innovation in the halal beauty industry.